Consumer Responses to Scarcity Appeals in Online Ordering - Nanik Hariyana; Wilma Cordelia Izaak; Dienni Ruhjatini Sholihah (Future Science, 2023)
Scarcity appeals, which highlight how a commodity or service is scarce due to